Dignidade restituída: o sofrimento inerente ao trabalho nas organizações como fator de mudança organizacional - Garcia, Ezequias dos Santos (2013)
This professional Master s dissertation deals with the following theme: dehumanizing nature of work in organizations of production and consumption in the context of industrialized society and technology. The research is done by means of literature delineating the research object through a clipping historical and sociological analysis of the concept of work inserted in the historical and social transformations of the industrial revolutions of modern thought and progress in those sectors of production and consumption . Therefore, the questions for the development of work in capitalist society, the factors that indicate the dehumanization of work within organizations, the influence of society on organizational models and management models that have been proposed throughout history organizations provide delineation methodological research. Due to this framework brought some conclusions, among which we highlight: the influence of Protestantism. From this religiosity gains a new sense of personal relationship with God, and the Christian life is to be lived and experienced in the world. The work is a duty, a service to God and to men and laziness must be rejected. On the other hand, precisely in the Industrial Revolution that the work will be consolidated as a factor of suffering. There is a whole historical development, for example, takes the field worker and puts in the industry. And the industry is that he knows the suffering. Suffering reaches the worker in its entirety, from various aspects of life in the industries and organizations of capitalist production: The work environment, routine and repetition, omission of suffering in the workspace for companies. Thus, it was concluded that the human dignity transcends your desktop, and your happiness involves a lifetime.